Are foreign-born workers more likely to make multiple injury claims than native-born workers?. (November 2020) - Xiang, Jianjun; Mittinty, Murthy; Liu, Zhidong; Tong, Michael Xiaoliang; Du, Mi; Pisaniello, Dino; Bi, Peng
Highlights: Foreign-born workers were less likely to make a repeat claim than native workers. Foreign-born workers were generally less likely to have time off work. The time interval of repeat claims was shorter in foreign-born workers. Repeat claims indicates room for improvement to reduce work-related injuries. Abstract: Several studies have explored the factors associated with repeat workers' compensation claims, however, none investigated the impact of migration status on repeat claims among injured workers. Using South Australian workers' compensation claims data from 2000 to 2014, generalized estimating equation models were used to compare the differences in repeat claims between foreign-born workers (FBW) and Australian-born workers. Time intervals between repeat claims, compensation costs, and working days lost by region of birth, as well as the change of severity between repeat claims were examined. Amongst 464, 596 accepted compensation claims, repeat claims for FBW (50.5%) was lower than that of Australian-born workers (57.4%, incidence-rate ratio, IRR = 0.83, 95% CI 0.82–0.84). However, region-specific analysis showed that European-born migrant workers were 19% more likely to make repeat claims than Australian-born workers (IRR = 1.19, 95% CI 1.17–1.22), including burns, digestive diseases, fractures, infectious diseases, mental disorders, musculoskeletal diseases, and skin injuries. The time interval between repeat claims was shorter for FBW compared to Australian-born workers and compensation payments of repeat claims were higher. Regardless of birth region, time intervals between repeat claims showed a decreasing temporal trend, while it was the opposite in terms of injury severity. Foreign-born workers were generally less likely to make a repeat claim than Australian-born workers, but with birth region differences. This may be attributable to underreporting from some workers. Foreign-born workers were generally less likely to have time off work but the overall costs were higher. These differences should be considered in future injury prevention strategies.